2012
DOI: 10.1007/s00268-012-1788-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Axillary Lymph Nodes and Tumor Size in Breast Cancer Compared with Histopathological Examination: A Population‐Based Analysis of 2,537 Women

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
(40 reference statements)
2
19
1
Order By: Relevance
“…Regarding concern with surgical overtreatment, patients with cT 1/2 N0 preoperative staging (fulfilling Z0011 eligibility criteria) but positive AUS‐FNAC/B who were referred directly to ALND (16 patients), 11 patients only had 1 or 2 metastatic LN and no extracapsular extension in the surgical specimen, meaning they might have been spared ALND (11 of 16, 69%). We report lower sensitivity than published in the literature for both PE, ranging between 25% and 35%, and AUS, between 54% and 92% . One possible explanation maybe that our patient population includes mostly early‐stage patients treated by surgery as a first treatment.…”
Section: Patient and Tumor Characteristicscontrasting
confidence: 65%
“…Regarding concern with surgical overtreatment, patients with cT 1/2 N0 preoperative staging (fulfilling Z0011 eligibility criteria) but positive AUS‐FNAC/B who were referred directly to ALND (16 patients), 11 patients only had 1 or 2 metastatic LN and no extracapsular extension in the surgical specimen, meaning they might have been spared ALND (11 of 16, 69%). We report lower sensitivity than published in the literature for both PE, ranging between 25% and 35%, and AUS, between 54% and 92% . One possible explanation maybe that our patient population includes mostly early‐stage patients treated by surgery as a first treatment.…”
Section: Patient and Tumor Characteristicscontrasting
confidence: 65%
“…8 Patients with palpable adenopathy at presentation are at risk for harboring heavier nodal disease burden, have confirmation of nodal metastasis by needle biopsy, and are managed with either upfront axillary lymph node dissection (ALND) or, increasingly, neoadjuvant chemotherapy. 9 In contrast, cN0 patients comprised the study populations that established the safety of SLNB alone for micro- and macro-metastatic axillary disease 2,5,9-11 , and are frequently spared the morbidity of ALND. 12 Therefore, the accuracy of the surgeons' nodal exam at presentation is paramount in allocating patients to the appropriate axillary treatment.…”
Section: Introductionmentioning
confidence: 99%
“…PE alone to determine axillary nodal involvement in breast cancer patients has a poor positive predictive value. The sensitivity and specificity of PE have been shown to be 30% and 93% in one study, and others have demonstrated a false‐positive rate of 53% . The use of AUS with PE has been shown to improve the accuracy of pretreatment nodal evaluation, with the sensitivity and specificity being 59% and 89%, respectively .…”
Section: Discussionmentioning
confidence: 96%